KENDALA IMPLEMENTASI ETIKA MORAL DAN AKHLAK (Sebuah Kajian Teoritis) - Hayumuti Hayumuti; Moch Charis Hidayat (Murabby: Jurnal Pendidikan Islam, 2019)
: Awareness the importance of moral ethics is not considered at this time. The situations can be seen from the existence of various social deviations in society. The rapid information flow spreads into one of the triggers of the problem. The purpose of this study is to describe the various obstacles that arise in the implementation of moral ethics, and find solutions that can help in handling these constraints. The method used in solving the problems that arise yag the library research is based on the form of the study of supporting theories obtained. Faced with various problems that arise, it takes a lot of effort in civilizing moral ethics in Indonesia so as not influenced by the entry of western culture.Basically the teaching of moral ethics can be applied to children from an early age. In the application there are various obstacles faced by parents and teachers in teaching. Ethical morals are much ruled out because they are considered not to impact on one's success. Whereas moral ethics are applied can help a person achieve good qualities of self. Various efforts can be made to teach moral ethics to the child. Character education is the answer in overcoming the problem. Character education will not only be education about moral ethics, values and religious. Character education has a higher meaning and not just teach what is right and what is wrong. The embedded character is more into the custom. Habits are continuously done by the child. Teaching related to character education is the responsibility of parents, schools, communities, and countries. In the application of its efforts certainly appear various obstacles that can not be ruled out. The biggest problem is the young generation who are less learning and willing to apply moral ethics. Nevertheless, it takes a positive spirit to constantly teach it to the younger generation and to use various innovations of moral ethics. It is expected that moral ethics are not only studied but also become an individual habit. The results showed that various experts support the assertion that character education plays a role in the application of moral ethics. So it can be concluded that character education can be applied in an effort to overcome various obstacles that arise in the implementation of moral ethics to the child.